PHYTOPLANKTON COMMUNITIES OFA FLOODPLAIN LAKE OF THE BRAHMAPUTRA RIVER BASIN, UPPER ASSAM B. K. - Sharma, B. K. (Journal of Indian Fisheries Association, 2015)
Phytoplankton (52 species; Bacillariophyceae > Chlorophyceae >Cyanophyceae > Euglenophyceae = Dinophyceae) of Samuajan heel, a tropicalfloodplain lake, registered identical mean annual richness (30 ± 4 species) inlittoral and limnetic regions and depicted 33.3 - 77.2 % and 31.4 - 81.1 %community similarities respectively. Their abundance ranged between 137 ±54 nil in littoral (Bacillariophyceae > Chlorophyceae) and 122 ± 45 nil(Chlorophyceae > Bacillariophyceae) in limnetic communities, comprisedabout 46% of net plankton and indicated winter peaks. This study depictedmoderate species diversity, high evenness and low dominance ofphytoplankton; species diversity showed significant direct correlation withrichness and evenness and an inverse relationship with dominance.Phytoplankton showed significant positive relationship with transparencyand silicate and negative with water temperature, rainfall, chloride andnitrate. Multiple regression revealed that ten abiotic factors accounted for> 80 - 98% of density variations of phytoplankton and the dominant groups.AN OVA depicted trends of significance in abundance of the biotic communitiesanalysed.Keywords: Phytoplankton, floodplain lake, Brahmaputra basin, abundance,ecology